USM STRENGTHENS INNOVATION AND COMMERCIALISATION EFFORTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 26 October 2015 – The Innovation and Commercialisation Office (ICO) of Universiti Sains Malaysia (USM) continues to strengthen the innovation and commercialisation efforts of the existing research products.